Open quadricepsplasty in hyperextension deformity of knee in children with arthrogryposis - Sananta, Panji; Dradjad, Respati Suryanto; Nurandani, Fiki (International Journal of Research in Medical Sciences, 2019)
Arthrogryposis includes heterogeneous disorders, characterized by congenital contractures of multiple joints. Knee involvement is very common (38–90 % of patients with amyoplasia) ranging from soft-tissue contractures (in flexion or hyperextension) to subluxation and dislocation. Children who present late will require surgery involving quadricepsplasty or lengthening of the contracted quadriceps muscle. Curtis and Fisher describe an open V-Y lengthening of the quadriceps femoris with post-operative immobilization in 30-45 ° of flexion. The main issue of this technique was limited degree of flexion that can be achieved, and the fibrous replacement of the quadriceps muscle. This is a neglected case of hyperextension deformity and congenital dislocation of knee in children with arthrogryposis resistant to conservative management and successfully treated by open quadricepsplasty.